The Effect of the Unpredicted Circumstances Theory on the Execution of the Administrative Contract -Comparative Study- - Mana, Abdelhafid; Hamli, Mohamed (Journal of Legal Studies and Researches, 2022)
Sometimes, while executing an administrative contract, some unexpected circumstances may happen; and would expose the contractor to serious financial losses if he continued the execution of this contract, what obliges the administration to provide an economic aid to the contractor in order to ensure the good and continuous functioning of the public establishment, and by consequence achieving the public interest. In fact, that solution was approved by the judiciary.